pdf ANALYSIS OF CONSUMER INTENTION TO PURCHASE SMART ROBOTIC PRODUCTS AND SERVICES IN INDONESIA: A THEORY OF PLANNED BEHAVIOR APPROACH - Aripin, Zaenal; Faisal, Ijang; Redjeki, Finny (KRIEZ ACADEMY : Journal of development and community service, 2024)
This research aims to investigate how consumers' perceptions of their control over the use of intelligent robotic technology influence their purchase intentions in the Indonesian market. Using the theory of planned behavior (TPB) approach, this study analyzes the relationship between perceived behavioral control (PBC), attitudes, purchase intentions, and contextual factors in consumer decision making regarding the adoption of this new technology. The research method used is a literature study which combines empirical research related to consumer behavior theories, as well as analysis of the social and cultural context in Indonesia. The main findings indicate that high perceived control over the use of intelligent robotic technology is significantly associated with positive attitudes toward the technology, which in turn contributes to consumers' purchase intentions. Contextual factors such as social influences from family, friends, and social media also moderate the relationship between PBC and consumer purchase intentions. The strategic implications of these findings highlight the importance of developing products that facilitate consumer use and understanding of this technology, as well as effective marketing strategies to build positive perceptions of control in a heterogeneous market such as Indonesia.